The semiotic construction of bourgeois femininity: A peircean analysis of social identity in Monet’s Woman with a Parasol - Santoso, Niky Putri; Muntazori, Ahmad Faiz; Amzy, Nurulfatmi (Jurnal Desain, 2025)
This study deconstructs the visual representation of 19th-century French social identity through a Peircean semiotic analysis of Claude Monet’s masterpiece, Woman with a Parasol (1875). While traditional art criticism often views the work as a spontaneous impression of light, this research reveals a deliberate semiotic construction of bourgeois femininity. Using Charles Sanders Peirce’s triadic model—specifically the Proposition → Indexical → Legisign framework—the study examines how visual elements such as the parasol, the white summer dress, and the low-angle perspective function as signs of social status and gender roles. The analysis finds that the painting serves as a visual claim for the 'leisure class' identity, where the female figure (Camille) is elevated both physically and psychologically as a symbol of domestic harmony and modern urbanity. By mapping the interaction between spontaneous brushstrokes (index) and rigid social conventions (legisign), this research concludes that Monet’s impressionism is not merely a formal innovation but a manifestation of the cultural ideology of the 19th-century French bourgeoisie. These findings provide critical insights for visual communication design in understanding how aesthetic choices can be used to construct and communicate complex social identities.